Plasma C-reactive protein levels in bipolar depression during cyclooxygenase-2 inhibitor combination treatment. (July 2018) - Edberg, David; Hoppensteadt, Debra; Walborn, Amanda; Fareed, Jawed; Sinacore, James; Halaris, Angelos
Abstract: Immune system activation and neuroinflammation appear to play a key role in the pathophysiology and treatment of bipolar depression (BDD). This study is the first to analyze blood levels of the pro-inflammatory biomarker C-reactive protein (CRP) in bipolar disorder patients treated with the cyclooxygenase-2 inhibitor, celecoxib (CBX). In this double-blind study, 47 consenting patients with BDD were randomized to receive either escitalopram (10 mg twice/day) + CBX (200 mg twice/day), or escitalopram (10 mg twice/day) + placebo (twice/day). Plasma CRP levels were measured in both patient groups at baseline, week 4, and week 8, and in a healthy control (HC) group of subjects (N = 35) once. Symptoms were rated using the 17-item Hamilton Depression Scale (HAMD-17). The CBX group had significantly lower HAMD-17 scores vs. placebo at week 4 (P = 0.026) and week 8 (P = 0.002). Therefore, SSRI + CBX is more effective than SSRI + placebo in reversing treatment resistance and augmenting antidepressant response in BDD. Baseline CRP levels were significantly increased amongst BDD patients versus HC subjects, indicating that CRP may be a useful biomarker for BDD (P = 0.044). No significant differences in CRP levels were measured between CBX and placebo groups at baseline (P = 0.156), but by week 8 CRP was significantly decreased in the CBX group vs. placebo (P = 0.003). This indicates reduced inflammation in CBX-treated patients, and that CRP may be a useful biomarker for monitoring treatment response in BDD patients during SSRI + CBX combination treatment. CRP and IL-6 levels were positively correlated in the CBX group, and CRP levels were positively correlated with BMI.